Masked hypertension : review and analysis of a subpopulation of outpatients from the hypertension consultation of Hospital Santa Maria - Oliveira, Adriana Isabel Maio (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2022